The Kingdom of Sriwijaya in History Textbooks in High School: Kerajaan Sriwijaya dalam Buku Teks Sejarah di SMA - Nur Syafarudin; Zamhari, Ahmad; Suriyadi, Aan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
History textbooks are a learning resource for students among the materials of the Sriwijaya Kingdom. The Kingdom of Sriwijaya was centered on the banks of the Musi River, Palembang developed from the 7th to the 13th century AD as one of the maritime kingdoms in the archipelago. This study aims to find out the content of the values of the Sriwijaya Kingdom in the history textbook in high school in the 2013 Curriculum revised 2017 class X and the 2021 edition of the Independent Learning Curriculum class XI. The research method used is qualitative descriptive, with data collection techniques in the form of observation, interviews, and documentation. Data analysis uses the discourse analysis of Teun A. van Dijk's theory which includes the text dimensions of microstructure, macro, and superstructure. The results of the study show that high school history textbooks, both the 2013 Curriculum and the 2021 edition of the Independent Curriculum with the theme of the Sriwijaya Kingdom, contain values including the value of diplomatic relations for political power in expanding influence and maintaining power stability. Community social values play an important role in improving the economy and trade. The cultural value of Mahligai Stupa building shows high cultural value. The value of language for social interaction can be seen in the inscriptions that use the Pallawa language of the Old Malay script. Buddhism reflects spiritual values that are an integral part of people's social lives. It can be concluded that the values of the Sriwijaya Kingdom reflected in history textbooks are diplomatic, political, social, cultural, linguistic, economic, and religious values.